Laves phase reinforced wear-resistant high-entropy alloy and preparation method thereof
By introducing Hf elements on the basis of the FCC phase formed by Fe, Co, Ni and V, a two-phase structure between the Laves phase and the FCC phase is formed, the problem of insufficient strength and oxidation resistance of existing wear-resistant materials in high temperature environments is solved. High entropy alloys with high yield strength and good wear resistance are achieved.
Patent Information
- Application Number
- CN202411617731.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
AI Technical Summary
The existing wear-resistant materials have insufficient strength and oxidation resistance in high temperature environments, making it difficult to bear the wear task in harsh environments.
By introducing Hf elements on the basis of the FCC phase formed by Fe, Co, Ni and V, a biphasic structure between the Laves phase and the FCC phase is formed, and the strength and wear resistance of the alloy are improved.
The high yield strength and good wear resistance of high entropy alloys are achieved, and the comprehensive mechanical properties and work hardening capabilities of the material are enhanced.
Smart Images

Figure CN119433323A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy alloys, and in particular to a Laves phase enhanced wear-resistant high entropy alloy and a preparation method thereof. Background Art
[0002] With the application of metal materials in aerospace, nuclear industry and other fields in recent years, their wear behavior at high temperature has begun to attract widespread attention. For example, the requirements for engines in the military and civil aerospace fields are constantly increasing, and the operating conditions of engines are also becoming increasingly harsh, such as high temperature, high pressure, high load, and foreign matter wear parts and other performance. High-temperature friction and wear is an important reason for the decline in performance, life and reliability of key parts of aircraft engines, so wear-resistant materials are extremely important.
[0003] At present, common wear-resistant materials are mainly nickel-based alloys and titanium alloys, but the manufacturing process of nickel alloys is complicated and the processing technology is complex; while the strength and oxidation resistance of titanium alloys in medium and high temperature environments are poor. Therefore, titanium alloys are difficult to undertake the task of wear resistance in harsh environments.
[0004] Due to its high entropy effect, severe lattice distortion effect, slow diffusion effect and cocktail effect, the technicians in this field proposed to use high entropy alloy as wear-resistant material, which is expected to solve the above technical problems. In the prior art, the main high entropy alloy used is CrMnFeCoNi high entropy alloy. CrMnFeCoNi high entropy alloy has a face-centered cubic structure, which helps to improve the plasticity of the overall high entropy alloy, so that CrMnFeCoNi high entropy alloy has good toughness; and the presence of the face-centered cubic structure also enables CrMnFeCoNi high entropy alloy to better bear the load and reduce wear during friction and wear, so that CrMnFeCoNi high entropy alloy also shows good wear resistance to a certain extent. However, the strength of the face-centered cubic structure is poor, and it may deform during actual application, causing the engine to malfunction. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a Laves phase enhanced wear-resistant high entropy alloy and a preparation method thereof. The present invention introduces Hf element on the basis of the FCC phase formed by Fe, Co, Ni and V, so that the Hf element can further form a Laves phase with Fe, Co and Ni, and the formed Laves phase and FCC phase are interlaced to effectively improve the strength of the alloy, so that the wear-resistant high entropy alloy prepared by the present invention has good wear resistance and high yield strength.
[0006] A Laves phase enhanced wear-resistant high entropy alloy and a preparation method thereof of the present invention are achieved by the following technical solutions:
[0007] The present invention takes into account that the alloy materials used in the parts in the prior art may produce cracks on the sub-surface of the material during the friction and wear process under certain conditions, which may lead to failures such as fatigue fracture of the material and severe wear behavior. In order to improve the wear resistance of the parts, the present invention provides a Laves phase enhanced wear-resistant high entropy alloy. The wear-resistant high entropy alloy is made of the following elemental components in terms of atomic mass percentage:
[0008] 23% to 23.375% Fe, 23% to 23.375% Co, 23% to 23.375% Ni, 23% to 23.375% V and 6.5% to 8% Hf, totaling 100%.
[0009] It should be noted that the present invention selects Fe, Co, Ni, V and Hf as alloying elements of high entropy alloy, wherein the addition of Fe can promote the formation of Laves phase and improve the alloy performance balance. Co is mainly used to stabilize the phase structure of high entropy alloy so that it can still maintain good performance under harsh environment. Ni can play a role in improving toughness. The purpose of V addition is mainly to refine the grains, thereby improving the wear resistance of the high entropy alloy. The addition of Hf can improve the hardness and wear resistance of high entropy alloy.
[0010] In the wear-resistant high-entropy alloy of the present invention, Fe, Co, Ni and V directly form an FCC phase as a matrix, and the introduction of the Hf element can further form a Laves phase with Fe, Co and Ni, thereby obtaining a dual-phase structure in which a face-centered cubic FCC phase and a Laves phase coexist.
[0011] And the present invention, by limiting each element within the above range, can make the microstructure of the wear-resistant high entropy alloy of the present invention form a stable face-centered cubic structure FCC phase and Laves phase coexisting dual-phase structure. Laves phase as a strengthening phase in the FCC phase matrix, the spinodal decomposition organization and the ordered atomic clusters pinning the dislocations change the slip mode of the dislocations, improve the work hardening ability of the alloy, can effectively improve the strength of the alloy, and change the size, morphology, distribution state has the potential to further improve the comprehensive mechanical properties of the alloy, for example, the wear-resistant high entropy alloy prepared by the present invention has more excellent plastic deformation ability and subsequent work hardening ability than most high entropy alloys, and has good machining ability and performance development potential.
[0012] The present invention also provides a method for preparing the above-mentioned wear-resistant high-entropy alloy, comprising the following steps:
[0013] Step 1, weigh each preparation raw material:
[0014] According to the element composition ratio of the wear-resistant high-entropy alloy, corresponding masses of preparation raw materials: single substance Fe, single substance Co, single substance Ni, single substance V and single substance Hf are weighed and set aside.
[0015] It should be noted that the present invention takes into account that the smaller the particle size of the raw material, the more conducive it is to fully mix the raw materials. However, if the particle size is too small, for example, if each raw material is added in the form of metal powder, when the vacuum melting furnace is subsequently evacuated, a part of the metal powder may be taken away, resulting in the inability to effectively synthesize the required wear-resistant high-entropy alloy. Therefore, the present invention preferably adds the elemental Fe, elemental Co, elemental Ni, elemental V and elemental Hf in the form of corresponding metal particles, so that the refractory metal Hf is melted and fully mixed with other metals. And the purity of the metal particles corresponding to each raw material used in the present invention is ≥99.99%.
[0016] Step 2, place the prepared raw materials:
[0017] Weighed single element Fe, single element Co, single element Ni, single element V and single element Hf are placed in the same melting pit of a vacuum arc melting furnace, with single element V placed at the bottom layer and single element Hf placed at the top layer.
[0018] It should be noted that the present invention takes into account the different melting points of various elements. When placing the various raw materials, the single element V is placed on the bottom layer, the single element Hf is placed on the top layer, and other metal elements are placed between the single element V and the single element Hf, so that the various raw materials can be mixed evenly in the subsequent smelting process.
[0019] In some preferred embodiments of the present invention, the elemental Fe, elemental Co, elemental Ni, elemental V and elemental Hf are placed in the same melting pit in order from bottom to top according to the melting point from low to high, so as to ensure that each prepared raw material is fully mixed in the subsequent smelting process to improve the uniformity of the alloy components.
[0020] Step 3, deoxygenation treatment:
[0021] Evacuate to vacuum degree ≤3×10 -3 Pa, followed by the introduction of argon;
[0022] Place titanium sponge in another melting pit and ignite an arc to melt the titanium sponge for 3 to 5 minutes.
[0023] It should be noted that in order to avoid oxidation of the prepared raw materials during the subsequent smelting process, the present invention also places sponge titanium in another melting pit and melts the sponge titanium for 3 minutes to 5 minutes by arcing to remove the residual oxygen in the furnace chamber.
[0024] Step 4, smelting treatment:
[0025] The raw materials for preparing the wear-resistant high-entropy alloy are smelted and cooled to obtain an alloy ingot.
[0026] It should be noted that the present invention firstly arc-melts the titanium sponge to remove the residual oxygen in the furnace chamber, and then performs a smelting process on the raw materials to prevent oxidation of the materials during the smelting process, thereby improving the quality of the high entropy alloy finally prepared.
[0027] In some preferred embodiments of the present invention, the raw materials are subjected to at least 6 smelting treatments, and each smelting treatment is performed until the raw materials are completely melted, and then cooled for 4 to 6 minutes, and then turned over before the next smelting treatment is performed to ensure that the raw materials are smelted more evenly to form an alloy ingot with uniform composition and organization distribution. In addition, during the smelting process, since the Laves phase and the FCC phase cannot be fused with each other, and the melting points of these two phases are different, the phenomenon of solidification occurs one after another, and finally a two-phase structure with both the FCC phase and the Laves phase is formed.
[0028] In some preferred embodiments of the present invention, a vacuum melting method is used for melting treatment, and the current during each melting treatment is 200A to 500A.
[0029] In some preferred embodiments of the present invention, the raw materials are subjected to 6 to 8 smelting processes.
[0030] Step 5, post-processing:
[0031] The alloy ingot is cut and then ground and polished to obtain the wear-resistant high-entropy alloy.
[0032] It should be noted that the present invention can cut the prepared alloy ingot according to actual needs to obtain alloy materials of required size and shape. In some preferred embodiments of the present invention, the cutting is performed using electric spark wire cutting technology.
[0033] Considering that there are a lot of cutting marks on the surface of the alloy material after cutting, which affects the experimental data, the surface is also ground and polished to remove the defects on the surface of the alloy after cutting.
[0034] In some preferred embodiments of the present invention, the grinding and polishing are carried out by the following steps: grinding with 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# WC sandpaper in sequence; polishing with 2.5W diamond polishing paste and red velvet polishing cloth until there are no scratches on the surface of the alloy ingot to obtain the wear-resistant high-entropy alloy.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention selects Fe, Co, Ni, V and Hf as alloying elements of high entropy alloy, wherein the addition of Fe can promote the formation of Laves phase and improve the alloy performance balance. Co is mainly used to stabilize the phase structure of high entropy alloy so that it can still maintain good performance under harsh environment. Ni can play a role in improving toughness. The purpose of V addition is mainly to refine the grains, thereby improving the wear resistance of the high entropy alloy. The addition of Hf can improve the hardness and wear resistance of the high entropy alloy.
[0037] The present invention limits the element composition of Fe, Co, Ni, V and Hf to 23% to 23.375% Fe, 23% to 23.375% Co, 23% to 23.375% Ni, 23% to 23.375% V and 6.5% to 8% Hf, totaling 100%, so that the microstructure of the wear-resistant high-entropy alloy of the present invention forms a stable face-centered cubic structure FCC phase and Laves phase coexisting dual-phase structure. The Laves phase as a strengthening phase has a spinodal decomposition organization in the FCC phase matrix and an ordered atomic cluster pinning effect on dislocations, which changes the slip mode of dislocations, improves the work hardening ability of the alloy, can effectively improve the strength of the alloy, and changes the size, morphology, and distribution state, which has the potential to further improve the comprehensive mechanical properties of the alloy. For example, the wear-resistant high-entropy alloy prepared by the present invention has a more excellent plastic deformation ability and subsequent work hardening ability than most high-entropy alloys, and has good mechanical processing ability and performance development potential.
[0038] In the wear-resistant high-entropy alloy of the present invention, Fe, Co, Ni and V directly form an FCC phase as a matrix, and the introduction of the Hf element can further form a Laves phase with Fe, Co and Ni, so that the FeCoNiVHf high-entropy alloy of the present invention is composed of an FCC phase matrix and a Laves strengthening phase, has a lower friction coefficient, a narrower wear scar width and excellent comprehensive mechanical properties.
[0039] According to the composition designed by the present invention, the FeCoNiVHf high entropy alloy prepared by the method of the present invention, the introduction of the Hf element generates a uniformly distributed Laves phase in the alloy, and the formed Laves phase and the FCC phase are intertwined, which can effectively improve the strength of the alloy, effectively disperse the friction force, reduce the tendency of brittle peeling of the worn surface, and finally improve the tribological properties of the alloy, so that the wear-resistant high entropy alloy material prepared by the present invention has a uniform composition, a lower friction coefficient and wear scar width, and good friction and wear properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 XRD patterns of the wear-resistant high entropy alloys of Examples 1 and 2.
[0041] Figure 2 This is the microstructure of the wear-resistant high entropy alloy of Example 1.
[0042] Figure 3 This is the microstructure morphology of the wear-resistant high entropy alloy of Example 2.
[0043] Figure 4 This is the microstructure morphology of the wear-resistant high entropy alloy of comparative example 1.
[0044] Figure 5 This is the microstructure morphology of the wear-resistant high entropy alloy of comparative example 2.
[0045] Figure 6 Room temperature friction and wear curves of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2.
[0046] Figure 7 This is the microscopic morphology image of the wear scar of the wear-resistant high entropy alloy of Example 1.
[0047] Figure 8 This is the microscopic morphology image of the wear scar of the wear-resistant high entropy alloy of Example 2.
[0048] Fig. 9 The wear scar microscopic morphology image of the wear-resistant high entropy alloy of Comparative Example 1 is shown in FIG.
[0049] Fig.10 This is the microscopic morphology image of the wear scar of the wear-resistant high entropy alloy of comparative example 2.
[0050] Fig.11 The Vickers hardness test results of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown.
[0051] Fig.12 The room temperature compressive stress-strain curves of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0052] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0053] Example 1
[0054] The present embodiment provides a wear-resistant high-entropy alloy. The wear-resistant high-entropy alloy of the present embodiment has a dual-phase structure in which a face-centered cubic structure FCC phase and a Laves phase coexist. The dual-phase high-strength and high-entropy alloy of the present embodiment is composed of the following element proportions in molar percentage: Fe: 23.375%, Co: 23.375%, Ni: 23.375%, V: 23.375% and Hf: 6.5%.
[0055] The preparation method of the wear-resistant high entropy alloy of this embodiment is as follows:
[0056] Step 1, weigh each preparation raw material:
[0057] According to the element composition ratio of the wear-resistant high-entropy alloy, corresponding masses of single-substance Fe metal particles, single-substance Co metal particles, single-substance Ni metal particles, single-substance V metal particles and single-substance Hf metal particles are weighed and set aside.
[0058] Step 2, place the prepared raw materials:
[0059] Weighed single-element Fe metal particles, single-element Co metal particles, single-element Ni metal particles, single-element V metal particles and single-element Hf metal particles are placed in the same melting pit of a vacuum arc melting furnace, with single-element V placed at the bottom layer and single-element Hf placed at the top layer.
[0060] Step 3, deoxygenation treatment:
[0061] Evacuate to vacuum degree ≤3×10 -3 Pa, followed by the introduction of argon;
[0062] Place titanium sponge in another melting pit and ignite an arc to melt the titanium sponge for 3 to 5 minutes.
[0063] Step 4, smelting treatment:
[0064] Each prepared raw material is smelted seven times, and each smelting treatment is performed until it is completely melted, followed by cooling for 4 to 6 minutes, and then flipped before the next smelting treatment. After cooling, an alloy ingot is obtained.
[0065] Step 5, post-processing:
[0066] 5.1) Using electric spark wire cutting technology, the alloy ingot is cut into samples of required size.
[0067] 5.2) Use 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# WC sandpaper for grinding, and then use 2.5W diamond polishing paste and red velvet polishing cloth to polish the sample surface without scratches, so as to obtain the wear-resistant high entropy alloy FeCoNiVHf 6.5 .
[0068] Example 2
[0069] The present embodiment provides a wear-resistant high-entropy alloy. The wear-resistant high-entropy alloy of the present embodiment has a dual-phase structure in which a face-centered cubic structure FCC phase and a Laves phase coexist. The dual-phase high-strength and high-entropy alloy of the present embodiment is composed of the following element proportions in molar percentage: Fe: 23%, Co: 23%, Ni: 23.375%, V: 23% and Hf: 8%.
[0070] The preparation method of the wear-resistant high entropy alloy of this embodiment is as follows:
[0071] Step 1, weigh each preparation raw material:
[0072] According to the element composition ratio of the wear-resistant high-entropy alloy, corresponding masses of single-substance Fe metal particles, single-substance Co metal particles, single-substance Ni metal particles, single-substance V metal particles and single-substance Hf metal particles are weighed and set aside.
[0073] Step 2, place the prepared raw materials:
[0074] Weighed single-element Fe metal particles, single-element Co metal particles, single-element Ni metal particles, single-element V metal particles and single-element Hf metal particles are placed in the same melting pit of a vacuum arc melting furnace, with single-element V placed at the bottom layer and single-element Hf placed at the top layer.
[0075] Step 3, deoxygenation treatment:
[0076] Evacuate to vacuum degree ≤3×10 -3 Pa, followed by the introduction of argon;
[0077] Place titanium sponge in another melting pit and ignite an arc to melt the titanium sponge for 3 to 5 minutes.
[0078] Step 4, smelting treatment:
[0079] Each prepared raw material is smelted seven times, and each smelting treatment is performed until it is completely melted, followed by cooling for 4 to 6 minutes, and then flipped before the next smelting treatment. After cooling, an alloy ingot is obtained.
[0080] Step 5, post-processing:
[0081] 5.1) Using electric spark wire cutting technology, the alloy ingot is cut into samples of required size.
[0082] 5.2) Use 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# WC sandpaper for grinding, and then use 2.5W diamond polishing paste and red velvet polishing cloth to polish the sample surface without scratches, so as to obtain the wear-resistant high entropy alloy FeCoNiVHf8.
[0083] Comparative Example 1
[0084] The present embodiment provides a wear-resistant high-entropy alloy. The wear-resistant high-entropy alloy of the present embodiment has a dual-phase structure in which a face-centered cubic structure FCC phase and a Laves phase coexist. The dual-phase high-strength and high-entropy alloy of the present embodiment is composed of the following elemental components in molar percentage: Fe: 25%, Co: 25%, Ni: 25% and V: 25%.
[0085] The preparation method of the wear-resistant high entropy alloy of this embodiment is as follows:
[0086] Step 1, weigh each preparation raw material:
[0087] According to the element composition ratio of the wear-resistant high-entropy alloy, corresponding masses of single-substance Fe metal particles, single-substance Co metal particles, single-substance Ni metal particles and single-substance V metal particles are weighed and set aside.
[0088] Step 2, place the prepared raw materials:
[0089] Weighed single-substance Fe metal particles, single-substance Co metal particles, single-substance Ni metal particles and single-substance V metal particles are placed in the same melting pit of a vacuum arc melting furnace, with single-substance V placed at the bottom layer and single-substance Co placed at the top layer.
[0090] Step 3, deoxygenation treatment:
[0091] Evacuate to vacuum degree ≤3×10 -3 Pa, followed by the introduction of argon;
[0092] Place titanium sponge in another melting pit and ignite an arc to melt the titanium sponge for 3 to 5 minutes.
[0093] Step 4, smelting treatment:
[0094] Each prepared raw material is smelted seven times, and each smelting treatment is performed until it is completely melted, followed by cooling for 4 to 6 minutes, and then flipped before the next smelting treatment. After cooling, an alloy ingot is obtained.
[0095] Step 5, post-processing:
[0096] 5.1) Using electric spark wire cutting technology, the alloy ingot is cut into samples of required size.
[0097] 5.2) Use 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, and 2000# WC sandpaper for grinding, and then use 2.5W diamond polishing paste and red velvet polishing cloth to polish the sample surface without scratches, so as to obtain the wear-resistant high entropy alloy FeCoNiV.
[0098] Comparative Example 2
[0099] The present embodiment provides a wear-resistant high-entropy alloy. The wear-resistant high-entropy alloy of the present embodiment has a dual-phase structure in which a face-centered cubic structure FCC phase and a Laves phase coexist. The dual-phase high-strength and high-entropy alloy of the present embodiment is composed of the following element ratios in molar percentage: Fe: 23.75%, Co: 23.75%, Ni: 23.75%, V: 23.75% and Hf: 5%.
[0100] The preparation method of the wear-resistant high entropy alloy of this embodiment is as follows:
[0101] Step 1, weigh each preparation raw material:
[0102] According to the element composition ratio of the wear-resistant high-entropy alloy, corresponding masses of single-substance Fe metal particles, single-substance Co metal particles, single-substance Ni metal particles, single-substance V metal particles and single-substance Hf metal particles are weighed and set aside.
[0103] Step 2, place the prepared raw materials:
[0104] Weighed single-element Fe metal particles, single-element Co metal particles, single-element Ni metal particles, single-element V metal particles and single-element Hf metal particles are placed in the same melting pit of a vacuum arc melting furnace, with single-element V placed at the bottom layer and single-element Hf placed at the top layer.
[0105] Step 3, deoxygenation treatment:
[0106] Evacuate to vacuum degree ≤3×10 -3 Pa, followed by the introduction of argon;
[0107] Place titanium sponge in another melting pit and ignite an arc to melt the titanium sponge for 3 to 5 minutes.
[0108] Step 4, smelting treatment:
[0109] Each prepared raw material is smelted seven times, and each smelting treatment is performed until it is completely melted, followed by cooling for 4 to 6 minutes, and then flipped before the next smelting treatment. After cooling, an alloy ingot is obtained.
[0110] Step 5, post-processing:
[0111] 5.1) Using electric spark wire cutting technology, the alloy ingot is cut into samples of required size.
[0112] 5.2) Use 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# WC sandpaper for grinding, and then use 2.5W diamond polishing paste and red velvet polishing cloth to polish the sample surface without scratches, so as to obtain the wear-resistant high entropy alloy FeCoNiVHf5.
[0113] Experimental Section
[0114] (I) Composition determination
[0115] The present invention conducts actual tests on the compositions of the wear-resistant high-entropy alloys prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2, respectively, and organizes the test results and their theoretical compositions as shown in Table 1.
[0116] Table 1 Theoretical and actual compositions of wear-resistant high entropy alloys
[0117]
[0118] It can be seen from the test results in Table 1 that the theoretical element content of the high entropy alloy prepared by the vacuum melting furnace is close to the actual element content, indicating that the composition of the high entropy alloy prepared by the vacuum melting furnace is relatively uniform.
[0119] (ii) XRD test
[0120] The present invention performs XRD tests on the wear-resistant high entropy alloys of Example 1 and Example 2, and the test results are as follows: Figure 1 shown.
[0121] Depend on Figure 1 It can be seen from the XRD spectrum of Example 1 that the diffraction peaks of the FCC phase and the Laves phase appear in the wear-resistant high-entropy alloy of Example 1, which indicates that the wear-resistant high-entropy alloy with coexistence of the FCC phase and the Laves phase is successfully prepared in Example 1. The diffraction peak of the σ phase can also be seen in the XRD spectrum of Example 1, but it is too similar to the FCC phase under an electron microscope, so it is regarded as the FCC phase.
[0122] Depend on Figure 1 It can be seen from the XRD spectrum of Example 2 that the wear-resistant high entropy alloy of Example 2 has diffraction peaks of FCC phase and Laves phase, which indicates that the wear-resistant high entropy alloy with coexistence of FCC phase and Laves phase is successfully prepared in Example 2. Compared with the XRD spectrum of Example 1, the number and peak intensity of diffraction peaks of Laves phase in Example 2 are increased, which indicates that when the content of Hf increases, it is conducive to the formation of Laves phase.
[0123] (III) Tissue morphology test
[0124] The present invention takes the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 as examples, and tests their organizational morphologies, and the test results are as follows: Figure 2-Figure 5 shown.
[0125] in, Figure 2 The microstructure morphology of the wear-resistant high entropy alloy of Example 1 shows that the wear-resistant high entropy alloy of Example 1 exhibits a eutectic structure, which is mainly a eutectic region of the FCC phase and the Laves phase.
[0126] Figure 3 The microstructure of the wear-resistant high entropy alloy of Example 2 shows that the wear-resistant high entropy alloy of Example 2 exhibits a hypereutectic structure, which is mainly composed of the Hf-rich Laves phase and the eutectic region of the FCC phase and the Laves phase. Figure 2 It can be seen that the amount of Laves phase increases significantly.
[0127] Figure 4 The microstructure morphology of the wear-resistant high entropy alloy of comparative example 1 is shown in FIG. 1 . It can be seen that the wear-resistant high entropy alloy of comparative example 1 exhibits V-poor FCC phase and V-rich FCC phase. Figure 2 As for the high entropy alloy without adding Hf, there is no Laves phase formed in its structure. Therefore, it can be known that the addition of Hf element introduces the Laves phase into the high entropy alloy.
[0128] Figure 5 The microstructure morphology of the wear-resistant high entropy alloy of comparative example 2 shows that the wear-resistant high entropy alloy of comparative example 2 exhibits a hypoeutectic structure, which is mainly composed of the FCC phase and the eutectic region of the FCC phase and the Laves phase. Figure 2 As can be seen, there are fewer Laves.
[0129] Based on the above, it can be known that the wear-resistant high-entropy alloy material structure prepared by the preparation method of the present invention will increase with the increase of Hf elements, and the Laves phase will also increase.
[0130] (IV) Friction performance test
[0131] The present invention takes the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 as examples, and respectively conducts friction performance tests on them. The friction performance test parameters are: load 10N, friction radius 2mm, wear time 30min, and the grinding material is GCr15. The test results are as follows Figure 6 shown.
[0132] Figure 6 is the room temperature friction and wear curve of the wear-resistant high entropy alloy of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and is Figure 6It can be seen that the wear-resistant high entropy alloys prepared in Examples 1 and 2 of the present invention have a lower friction coefficient, the friction coefficient of Comparative Example 1 is larger, and although Comparative Example 2 has a lower friction coefficient, its wear scar width is larger, so it is considered that its wear resistance is inferior to that of Examples 1 and 2.
[0133] The present invention also conducts microscopic morphology test on the samples obtained after the above friction performance test of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and the test results are as follows: Figure 7-10 shown.
[0134] in, Figure 7 This is the wear scar micromorphology image of the wear-resistant high entropy alloy of Example 1. It can be seen that its wear mechanism is mainly abrasive wear and fatigue wear.
[0135] Figure 8 This is the wear scar micromorphology image of the wear-resistant high entropy alloy of Example 2. It can be seen that its wear mechanism is mainly abrasive wear and fatigue wear, and the wear scar width is the smallest.
[0136] Fig. 9 The wear scar microscopic morphology image of the wear-resistant high entropy alloy of comparative example 1 is shown in FIG. Figure 7 As for the wear scar microscopic morphology image of Example 1, the wear scar width of Comparative Example 1 is significantly increased. This may be because Comparative Example 1 lacks the Hf element and does not generate Laves. Therefore, the wear-resistant high entropy alloy of Comparative Example 1 mainly exists in the FCC phase, resulting in a lower hardness of the alloy material.
[0137] Fig.10 The wear scar microscopic morphology image of the wear-resistant high entropy alloy of comparative example 2 is shown in FIG. Figure 7 As for the wear scar microscopic morphology image of Example 1, the wear scar width of Comparative Example 2 is also significantly increased. This may be because although Hf element is added to Comparative Example 2, the content of Hf element is relatively small compared to that in Example 1, resulting in limited Laves phase formation, which cannot effectively improve the wear resistance of the alloy.
[0138] according to Figure 6 as well as Figure 7-10 The friction coefficient and wear scar width of the wear-resistant high entropy alloy materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 obtained from the test results are summarized as shown in Table 2.
[0139] Table 2 Friction coefficient and wear scar width of Example 1, Example 2, Comparative Example 1 and Comparative Example 2
[0140] Friction coefficient Wear scar width / μm Example 1 0.5544 410.75 Example 2 0.6341 399.07 Comparative Example 1 0.6704 1048.00 Comparative Example 2 0.6123 517.13
[0141] It can be seen from the test results in Table 2 that the wear-resistant high entropy alloy materials prepared in Examples 1 and 2 of the present invention have smaller friction coefficients and wear scar widths.
[0142] By comparing the friction coefficient and wear scar width test results of Comparative Example 1 and Example 1, it can be seen that when the Hf element is not added to the wear-resistant high-entropy alloy, the friction coefficient and wear scar width of the high-entropy alloy are significantly increased, indicating that the strength of the single FCC phase is low, and it is easier to produce severe plastic deformation during the friction and wear process, resulting in strong stratification of the friction layer. The addition of the Hf element introduces the Laces phase into the high-entropy alloy. The Laves phase has a higher strength, and therefore its wear resistance is greatly improved.
[0143] By comparing the friction coefficient and wear scar width test results of Comparative Example 2 and Example 1, it can be seen that an appropriate amount of Hf element will form a eutectic structure in which FCC phases and Laves phases are interlaced, and the layered structure can make the FCC / Laves phases with different hardnesses undergo uniform cooperative plastic deformation under external stress. This cooperative deformation ability can effectively disperse the friction force, reduce the tendency of brittle peeling of the worn surface, and ultimately improve the tribological properties of the alloy.
[0144] Based on the above, it can be seen that the wear-resistant high entropy alloy material prepared by the present invention has uniform composition, low friction coefficient and wear scar width, and good friction and wear performance.
[0145] (V) Mechanical properties test
[0146] The present invention takes the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 as examples, and conducts Vickers hardness and compressive stress-strain performance tests on them, and the test results are as follows: Fig.11 and Fig.12 shown.
[0147] The present invention uses a HV-1D / 1MD micro Vickers hardness tester to perform hardness testing and a SUNSUTM5105 electronic universal testing machine to perform compressive stress-strain performance testing.
[0148] Fig.11 The Vickers hardness test results of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 show that the wear-resistant high entropy alloy materials of Example 1 and Example 2 have higher hardness, and the overall hardness increases with the increase of Hf element. The hardness of Comparative Example 1 is poor, and the hardness of Example 2 is the highest.
[0149] Fig.12The room temperature compressive stress-strain curves of the wear-resistant high entropy alloys of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 show that Example 1 has a relatively high yield strength and also has a certain plasticity, and Example 2 has a higher yield strength. Comparative Example 1 has the highest strength but the worst plasticity. Example 2 has the best plasticity but the lowest strength.
[0150] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A Laves phase enhanced wear-resistant high entropy alloy, characterized in that: The wear-resistant high entropy alloy is made of the following elemental components in terms of atomic mass percentage: 23% to 23.375% Fe, 23% to 23.375% Co, 23% to 23.375% Ni, 23% to 23.375% V and 6.5% to 8% Hf, totaling 100%; The microstructure of the wear-resistant high-entropy alloy is a dual-phase structure in which a face-centered cubic FCC phase and a Laves phase coexist.
2. The Laves phase enhanced wear-resistant high entropy alloy according to claim 1, characterized in that: The Laves phase is mainly composed of Fe, Co, Ni and Hf elements.
3. The Laves phase enhanced wear-resistant high entropy alloy according to claim 1, characterized in that: The face-centered cubic structure FCC is mainly composed of Fe, Co, Ni and V.
4. A method for preparing the Laves phase enhanced wear-resistant high entropy alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the element composition ratio of the wear-resistant high-entropy alloy, weigh the corresponding mass of the preparation raw materials: single substance Fe, single substance Co, single substance Ni, single substance V and single substance Hf, and set aside; Weighed single element Fe, single element Co, single element Ni, single element V and single element Hf are placed in the same melting pit of a vacuum arc melting furnace, with single element V placed at the bottom layer and single element Hf placed at the top layer; sponge titanium is placed in another melting pit; Arc melting titanium sponge for 3-5 minutes to remove residual oxygen in the furnace chamber; The raw materials for preparing the wear-resistant high-entropy alloy are smelted and cooled to obtain an alloy ingot; The alloy ingot is cut and then ground and polished to obtain a Laves phase-enhanced wear-resistant high-entropy alloy.
5. The preparation method according to claim 4, characterized in that: The smelting treatment is performed at least 6 times, and each smelting treatment is performed until the smelting is completely melted, followed by cooling for 4 to 6 minutes, and then turning over before the next smelting treatment.
6. The preparation method according to claim 5, characterized in that: The current intensity during each smelting process is 200A to 500A.
7. The preparation method according to claim 4, characterized in that: The elemental Fe, elemental Co, elemental Ni, elemental V and elemental Hf are all added in the form of corresponding metal particles, and the purity of each of them is ≥99.99%.
8. The preparation method according to claim 4, characterized in that: The elemental Fe, elemental Co, elemental Ni, elemental V and elemental Hf are placed in the same melting pit in order from low to high melting points.
9. The preparation method according to claim 4, characterized in that: The grinding and polishing is carried out by the following steps: The alloy ingot is polished with 80#, 120#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500# and 2000# WC sandpaper in sequence; then, the alloy ingot is polished with 2.5W diamond polishing paste and red velvet polishing cloth until there are no scratches on the surface of the alloy ingot, thereby obtaining the wear-resistant high-entropy alloy.